2016
DOI: 10.5812/numonthly.40182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Toxoplasma gondii Antibodies in Hemodialysis Patients with Chronic Kidney Disease in Sari, Iran

Abstract: BackgroundToxoplasma gondii has worldwide distribution and is one of the most prevalent infectious agents in humans.ObjectivesThe aim of this study was to determine the prevalence of anti-Toxoplasma gondii antibodies in hemodialysis patients with chronic kidney disease (CKD) in the hemodialysis unit of Fatemeh Zahra hospital at the Mazandaran University of Medical Sciences in Sari, Iran.MethodsSeventy-three patients with CKD and 145 healthy volunteers were assessed for anti-Toxoplasma gondii (IgG, IgM, and IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(22 reference statements)
1
1
1
Order By: Relevance
“…In the control group of 64.7%, person had IgG antibody against T. gondii, and 0.7% were positive for IgM. This study revealed a high prevalence of T. gondii infection in hemodialysis patients, which is similar to findings in Turkey (76.5%) [28] and Iran (80.8%) [29], but higher than other reported studies in Iran (60.0%), Malaysia (51%), Mexico (10.0%) and Egypt (60%) [1,[9][10][11]. The significant differences in prevalence between the regions might be attributed to the differences in socioeconomic, cultural (cat ownership, personal hygiene, feeding habits) and perhaps climatic factors [30,31].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the control group of 64.7%, person had IgG antibody against T. gondii, and 0.7% were positive for IgM. This study revealed a high prevalence of T. gondii infection in hemodialysis patients, which is similar to findings in Turkey (76.5%) [28] and Iran (80.8%) [29], but higher than other reported studies in Iran (60.0%), Malaysia (51%), Mexico (10.0%) and Egypt (60%) [1,[9][10][11]. The significant differences in prevalence between the regions might be attributed to the differences in socioeconomic, cultural (cat ownership, personal hygiene, feeding habits) and perhaps climatic factors [30,31].…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of anti-Toxoplasma IgG antibody is positively associated to the duration of hemodialysis treatment [28,33]. However, in the present study in north of Iran, there was no significant difference between the duration of dialysis and toxoplasmosis IgG antibody and this has been reported in other local studies too [29,36]. Besides, the prevalence of toxoplasmosis was significantly higher in females than in males in the current investigations (P = 0.005).…”
Section: Discussioncontrasting
confidence: 75%
“…Of the 1,659 identified articles, 10 were included, and the results from these studies were weighted ( Table 1 ) [ 40 - 49 ]. One study was removed due to over-matching [ 50 ]. A flow diagram showing the study selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The study of Forough Kazemi, [20] , Al-Saadawi and Alkhaled [21] , Ayser and Abdul-Aziz [22] Bayani,M [23] ,Al-Dulaimi [24], Sharif Maraghi [25], recorded similar results of our current study. On the other hand, there are studies that differ with it Seyyedpour [26]. Among the hemodialysis patients, the results showed that the percentage of seropositivity was higher in males 17(40.47) than in females 15 (45.45) but the differences were not statistically significant , Jones [27] .…”
Section: Discussionmentioning
confidence: 97%